Development of Biology Learning Module Based on Local Potential Types of Fish in Sibolga Waters - Tanjung, Fatimah Prawita Putri Samri; Anas, Nirwana; Hutasuhut, Melfa Aisyah (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
Application of local values in Sibolga City in learning at school will certainly help students recognize local potential and the culture around it. Efforts where students are capable of knowing the scientific names of the types of fish around them. This experiment aims to describe the results of the development of a biological module based on the local potential of fish species in Sibolga waters to determine the development of a valid, practical, and effective module in animalia material. This research was conducted at Senior High School Darur Rachmad which is located at Kerala, Sibolga, Sambas, Sibolga City. The subjects studied were students of class X consisting of 30 students. This study uses the ADDIE development model, namely analysis, design, development, implementation, and evaluation. The instruments used in this research were questionnaires and pretest-posttest question sheets. Based on the research results, the N-gain score on the students' pretest and posttest was 0.77 with the high criteria. So, converted into a percentage to measure effectiveness, a value of 77% was obtained in the effective category. The results of research on the development of biology modules based on the local potential of fish species in Sibolga waters are expected to increase student achievement.